Efektivitas Media Short Movie dalam Meningkatkan Pengetahuan Safety Riding pada Pengemudi Wanita - Cyntia Finda Rizkyana; Dani Fitria Brilianti; Ahmad Basuki (Lembaga Pengembangan Kinerja Dosen, 2025)
Traffic accidents are one of the leading causes of death in Indonesia, particularly involving motorcycle riders. Female drivers are among the vulnerable groups because they often pay less attention to safety aspects such as wearing helmets, using turn signals, and obeying traffic signs. This study aimed to examine the effectiveness of short movie media in improving safety riding knowledge among PKK mothers in Tapelan Village. The research employed the Research and Development (RnD) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The subjects were 50 PKK mothers. The pre-test results showed an average knowledge score of 51.1%, which increased to 89.5% in the post-test, with an effectiveness rate of 79%. Short movie media was considered highly feasible as an educational tool because it effectively attracted attention and facilitated understanding of the material.